Ecological intelligence: a capacity united to environmental balance and human development within the sustainability framework (Dissertare, 2023)
The protection of the environment and the rational use of the resources that ecological systems provide to human beings have become a concern in this century, not only for education in general, but for environmental sciences and emerging disciplines such as pedagogy and environmental psychology. The latter, with significant contributions that refer to ecological intelligence, is defined by its precursor, Goleman (2009), as the ability to understand the effects, implications and consequences that human actions have on nature, allowing the individual to reformulate their lifestyles and transcend to the collective realization of strategies that minimize the damage caused to the ecological systems of the planet. The objective of this work is to analyze the definition and benefits of ecological intelligence, and the role of education in the development of this capacity and its contributions to sustainable development. It is proposed that ecological intelligence, when promoted educationally and socially, contributes to efforts unification,  the exercise of eco-environmental actions, ecological awareness consolidation, the development of a rational and conscious personality committed to integration and participation in the ecological systems preservation. It is concluded that environmental conservation requires the promotion of ecological intelligence that enhances the integral human development of future generations and the functional balance of nature as a result of education for sustainability.
Keywords: ecological intelligence; human development; environmental awareness; ecological systems; ecological education